José Agustín Blanco Barros (1922 – 2016) : Un Provinciano Universal - Patiño, Pedro Castellón (European Journal of Multidisciplinary Studies, 2018)
This article is part of an investigation about the life and work of the geographer and historian of the Colombian Caribbean José Agustín Blanco Barros. In this work, he realizes his initial intellectual formation in his Matria under the guidance of his father, José Agustín Blanco Vásquez, a philosopher and school teacher, of Eudist training at the Cartagena Seminary when he studied philosophy and with the Brothers of La Salle, Barranquilla. This served as the basis to become a protagonist of universal dimension.
Keywords: Provincial, Universal, Illustrated, Matria, Village